2000
DOI: 10.1007/s001010050830
|View full text |Cite
|
Sign up to set email alerts
|

Kognitive Störungen in der frühen postoperativen Phase nach Remifentanil/Propofol- und Sevofluran/Fentanylanästhesie

Abstract: The duration of cognitive impairment in the early postoperative period differed by the test procedures and the anaesthetic procedures used in this investigation. Recovery appeared to be faster after sevoflurane/fentanyl than after remifentanil/propofol at least in aspects of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
2
10
1
1
Order By: Relevance
“…Patients in both groups demonstrated significant delay in recovery of cognitive function, even 1.5 h after the end of anaesthesia, without any difference between the groups. In agreement with our results, Biedler et al [18] were able to detect impairment of cognitive function even 4 h after anaesthesia lasting < 1 h. It has been previously demonstrated that cognitive function is more rapidly restored after sevoflurane or desflurane anaesthesia than after propofol, but in those studies propofol was given with nitrous oxide, which might explain the different results [19]. Our data suggest that duration of anaesthesia, even with modern drugs such as propofol and sevoflurane, has an effect on the recovery of sophisticated cognitive functions that is often not realised in clinical practice.…”
Section: Discussionsupporting
confidence: 94%
“…Patients in both groups demonstrated significant delay in recovery of cognitive function, even 1.5 h after the end of anaesthesia, without any difference between the groups. In agreement with our results, Biedler et al [18] were able to detect impairment of cognitive function even 4 h after anaesthesia lasting < 1 h. It has been previously demonstrated that cognitive function is more rapidly restored after sevoflurane or desflurane anaesthesia than after propofol, but in those studies propofol was given with nitrous oxide, which might explain the different results [19]. Our data suggest that duration of anaesthesia, even with modern drugs such as propofol and sevoflurane, has an effect on the recovery of sophisticated cognitive functions that is often not realised in clinical practice.…”
Section: Discussionsupporting
confidence: 94%
“…In a geriatric population, maintenance of anesthesia with remifentanil-N 2 O, compared with isoflurane-N 2 O-fentanyl, showed shorter postoperative recovery of cognitive function, but the postoperative Mini-Mental State Examination scores equalized after 12 hours [20]. Recovery appeared to be faster after sevoflurane-fentanyl administration than after remifentanil-propofol administration, at least in aspects of cognitive function [21]. Although the use of remifentanil with lower concentrations of sevoflurane facilitates early recovery, it does not influence discharge time from the recovery ward [22].…”
Section: Discussionmentioning
confidence: 79%
“…This volatile anesthetic can have adverse postoperative cognitive behavioral effects that may affect task performance; its rapid elimination may also speed up the postoperative recovery time, which in turn could reduce the discharge time in large and overcrowded operating rooms (1)(2)(3). Both pharmacologic (4) and non-pharmacologic (5-8) interventions have been reported to reduce recovery times.…”
Section: Introductionmentioning
confidence: 99%